Experimental confirmation of efficient island divertor operation and successful neoclassical transport optimization in Wendelstein 7-X. (1st April 2022) - Sunn Pedersen, Thomas; Abramovic, I.; Agostinetti, P.; Agredano Torres, M.; Äkäslompolo, S.; Alcuson Belloso, J.; Aleynikov, P.; Aleynikova, K.; Alhashimi, M.; Ali, A.; Allen, N.; Alonso, A.; et al.
Abstract: We present recent highlights from the most recent operation phases of Wendelstein 7-X, the most advanced stellarator in the world. Stable detachment with good particle exhaust, low impurity content, and energy confinement times exceeding 100 ms, have been maintained for tens of seconds. Pellet fueling allows for plasma phases with reduced ion-temperature-gradient turbulence, and during such phases, the overall confinement is so good (energy confinement times often exceeding 200 ms) that the attained density and temperature profiles would not have been possible in less optimized devices, since they would have had neoclassical transport losses exceeding the heating applied in W7-X. This provides proof that the reduction of neoclassical transport through magnetic field optimization is successful. W7-X plasmas generally show good impurity screening and high plasma purity, but there is evidence of longer impurity confinement times during turbulence-suppressed phases.